The Relationship Between Blood Omega‐3 Levels and the Small Vessel Disease in Ischemic Stroke Patients: A Case‐Control Study - Leila Afshar Hezarkhani; Kamran Mansouri; Nader Salari; Mojtaba Ammari‐Allahyari; Hasti Shahbazi; Milad MohamadYari; Masoud Mohammadi (Health Science Reports)
ABSTRACT Background Stroke is one of the leading causes of death worldwide, and it can lead to the development of small vessel disease in the brain, which in turn exacerbates the unintended and long‐term consequences of this condition. Given that various factors are involved in the development and exacerbation of this disease, the aim of the present study is to determine the relationship between blood omega‐3 levels and the small vessel disease in ischemic stroke patients. Methods The present study is a case‐control study. The target population in this study consists of ischemic stroke patients enrolled in a hospital through a census over the course of 1 year. The sample size was 72 patients, who were assessed using MRI and/or CT scans for the extent of small vessel blood vessel changes. They were then divided into two groups: those with small vessel changes (31 individuals—cases) and those without small vessel changes (41 individuals—controls). Subsequently, individuals in both groups were evaluated for their blood omega‐3 levels. Statistical analysis was conducted using SPSS‐20. Results The research findings revealed that the majority of individuals in both the case and control groups were in the 51–70 age range and were female. Apart from the gender variable, the two groups did not significantly differ in other variables. Upon comparing the two groups, it was evident that men comprised a larger portion of the case group. Analytical findings also indicated a significant relationship between blood omega‐3 levels and small vessel changes in the brain. This is because the results of the mean blood omega‐3 levels of the two case and control groups showed a statistically significant difference between the two groups (p = 0.001 < 0.05). Conclusion Based on the research findings, there is an association between low levels of omega‐3 in blood and the occurrence of small vessel changes in the brain.